Behavioral responses of Australian fur seals (Arctocephalus pusillus doriferus) to environmental variations. Issue 3 (17th December 2013) - Garlepp, Linda; Logan, Murray; Kirkwood, Roger
Abstract Observing how pinnipeds respond to variations in climatic and oceanographic conditions informs marine managers on factors that could limit their range, foraging ability and breeding success. Here, we examine how Australian fur seals (Arctocephalus pusillus doriferus) at Seal Rocks, Victoria, Australia, responded to normal climatic conditions from August 2009 to January 2010, which included their Austral spring‐summer breeding period, to investigate their tolerances to a range of environmental stimuli. Seal numbers ashore and a range of climatic variables were collected hourly during daylight periods and compared using Generalized Additive Mixed Models (GAMMs). Air temperature was the most consistent predictor of haul‐out behavior, with seal numbers ashore declining as air temperature increased (effect size −50%, edf 1.00, P < 0.001). Increased wave height (effect size 74%, edf 1.00, P < 0.001) and wind speed (effect size 79%, edf 1.00, P < 0.001) were associated with increased seal numbers ashore. Potentially, higher air temperatures reduce the seals tolerance to remain out of the water, while high wind/wave action increases at‐sea metabolic costs. These results demonstrate how changes in climate could alter a seal's ability to remain ashore, to rest or breed, and its ability to forage effectively, thus driving changes in population status and range.